A realistic approach to radiation-induced treatment of micropollutants in wastewater - Genc, Aysenur; Ergun, Ece; Kantoglu, Oemer; İnce, Mahir; Acar, Orhan (Springer Int Publ Ag, 2024)
In this study, radiation-induced removal of micropollutants commonly found in real wastewater effluents was investigated. The study began by thoroughly developing a validated analytical methodology for the determination of 13 selected micropollutants in real wastewater effluent. It was found that the concentrations of 10 target micropollutants in effluent samples were found to be above the method detection limits. The samples were then exposed to gamma radiation at several doses ranging from 0 to 50 kGy. After 30 kGy irradiation, a decrease of 100%, 5%, and 43% was observed in color, pH, and TOC, respectively. When a dose of 10 kGy was applied, estrone, 17-beta-estradiol, and 4-octylphenol were not detected in irradiated wastewater samples. The removal efficiencies of other target micropollutants drastically increased with the increased dose up to 10 kGy for ibuprofen (86%), 20 kGy for diclofenac (93%), diphenylamine (79%), triclosan (98%), and bisphenol-A (97%), and 30 kGy for ketoprofen (78%) and diethyl phthalate (83%). The lowest absorbed dose required for 90% removal was found for triclosan (10.49 kGy). G-values, dose rates, and D0.5 and D0.9 doses depended on the initial concentration and molecular structure of the target micropollutants. In comparison with the literature data, the relatively high doses required to achieve high removal efficiencies indicate the competitive reactions for reactive species between the trace-level quantities of micropollutants and the matrix components in real wastewater. In light of this, it is suggested that research employing real wastewater samples rather than synthetic water provides more realistic results for radiation treatment applications.
Keywords: Micropollutants; Wastewater; Ionizing radiation; G-value; Liquid chromatography; Mass spectrometry